Pengaruh Waktu Dan Suhu Pencampuran Terhadap Derajat Grafting Maleated Natural Rubber Dengan Inisiator Benzoil Peroksida - Zuliarti, Indah; Khairat, Khairat; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Maleated natural rubber is modification of natural rubber with grafting polar fungsional of maleic anhydride. This research aim to learning effect of the reaction temperature and reaction time modified MNR with benzoyl peroxide. Benzoyl peroxide was used to initiate the free radical graft copolymerization. Process produced Maleated Natural Rubber were modifed at internal mixer reaction temperature and reaction time, which are variated by 150o C, 155o C, 160o C, and 165o C of reaction temperature, and 8, 10, 12, 14 minutes of reaction time. Amount of MAH 8 phr and 60 rpm rotor rate of internal mixer. Quantities of the grafted anhydride (MA) were determined by titration of the methanol. Initiator benzoyl peroxide of the grafted anhydride on natural rubber relatif not effected. Increasing temperatur and time reaction also causes increasing levels grafting until point of optimum. The results showed the optimum temperature is 160oC and reaction time is 12 minutes. produced 4,75% grafting.Keywords : benzoyl peroxide, grafting , maleic anhydric, maleated natural rubber, temperature